Some results of stability evaluation for the Song Tranh 2 dams and its surrounding geological environment by microseismic investigations - Lu, Ngo Thi; N.K., Kapustian; G.N., Antonovskaia; A.V., Danilov; I.V., Pudova; Tung, Nguyen Thanh; Hai, Nguyen Thanh; Khoi, Le Quang; Hang, Phung Thu (Vietnam Journal of Earth Sciences, 2015)
In this paper the authors present the results of evaluation of stability for the Song Tranh 2 dam and its surrounding geological environment. The study is carried out by using two modifications of microseismic observation. For the first modification the data were collected along 5 profiles distributed on land surface of the dam area and its surrounding. In the second modification the measurements were concentrated in the dam location with the microseismic signals generated by rotation of turbines of the electric power plant as an additional source. In this case the investigated profiles are distributed both on the top surface of the dam as well as along the tunnels constructed inside the dam body. The high value of the relative intensity of microseismic signals (The ratio of the microseismic wave amplitudes in a certain frequency band recorded by the movement and fixed stations obtained in this study are allowed us to reveal a number of heterogeneity objects distributed in the dam and its surrounding geological environment with define depth. The technique is more effectivle in the detection of subvertical contact. The correlation with the geological - geophysical available data is indicated the heterogeneities mostly are taken places where distributed tectonic fault or underground weak section. It will be very useful if the technique is applied for the study of the same problem for the other hydroelectric power plants in Vietnam. References Capustian N.K., Yudakhin F.N., 2007. Seismic study of man-made impacts on earth’s crust and their consequences. Ekatherinburg: UrO RAN, 416p (in Russian). Capustian N.K. Yudakhin F.N., 2009. The possibilities of micro-seismic research in study of geological environments and building constructions. Geological disasters, Аrkhangelck, IEPS, ANTS YrO RAN, pp. 209-212 (in Russian). Ngo Thi Lu, Capustian N.К., Antonovskaya G.N., Danilov, K.B., Danilov А.V., 2013. Complex of seismic techniques for survey of hydrological structures. Journal of civil construction "Construction materials, Moscow, pp. 36-39 (in Russian). Patent RU 2242033 ’Assessment methods and choices of land areas for construction of structures for various purposes’. Authos: Yudakhin F.N., Capustian N.К., Khoreev V.S., Antonovskaya G.N., Shakhova IE.V., 10.12.2004 year (in Russian). Patent RU 2365896 ’Method of determining the parameters of physical conditions of buildings and/or strcutures’. Authors: Yudakhin F.N, Capustian N. К., Antonovskaya G.N., Shakova IЕ.V., Basakina I.М., Yakovich А.А., 27.08.2009 year (in Russian) Manual of complex engineering seismometric and seismological monitoring the state of buildings and structures, including the sire of their placement, 2011. М. Publish. IFZ RAS, 36p (in Russian) Seismological research in the Artic and sub-Artic regions, 2011. Pod red. membe.-corr. RAS F.N. Yudakhin. Ekatherinburg: UrO RAS, 244p (in Russian). Fedotov S.A, Fedotova M.P. High-resolution multi-wave seismic and electrical technology for engineering studies. VNII Geophysics, Меtrogiprotranc, Moscow, p 3 (in Russian) Yudakhin F.N., Antonovskaya G.N., Shakhova, IE.V., Capustian N.К., 2004. A new way of experimental seismic survey of the mediam when placing objects of special importance. Technogenic seismicity in mining operations: pockets of model, forecast and prevention. Apatites: KNTS RAS, pp. 201-208 (in Russian). Yudakhin F.N., Capustian N.K., Fransuzova V.I., Antonovskaya, G.N., Shakhiva, IEV., Danilov, K.B., Ivanova IE.V., 2010. Using micro-seismic method for scientific and practical purposes. Structure, properties, dynamics and mineralogeny of lithosphere in the Eastern European platform: Mat. XVI Intern. conference, Scientific book. TP. Voronesh, pp 393-397 (in Russian)